Diversity of cyanobacteria in man-made solar saltern, Petchaburi Province, Thailand - A pilot study - Thomrat Chatchawan (2018)
Solar salterns can be found in many tropical and subtropical regions throughout the world, however, nothing is known from these habitats in Southeast Asia. The Petchaburi solar salterns are located in Petchaburi Province, middle part of Thailand. These areas can be defined as hypersaline biotopes where, in salt-producing times, salinity increases by more than 10 times that of seawater. The annual salinity gradient of these areas ranges from 0 - 35 ppt. in the non salt-producing period and gradually elevates from more than 35 ppt. up to saturation in the salt producing period, when salt crystals are formed. The cyanobacterial samples were collected from four ponds of the Petchaburi saltern during the salt producing period (November - December 2009), when the range of salinity was from 90 - 250 ppt. pH values of soil samples ranged from 7.9 - 8.1 and conductivity from 164 - 350 ds/m. Other physico-chemical parameters were analyzed in the soil samples as well. Cyanobacterial mats and their filaments predominated among the diatoms. Sixteen species of cyanobacteria were found. Dominant species were Spirulina subsalsa, Coleofasciculus cf. chthonoplastes and Oscillatoria lloydiana. Most of the species found in this study have not yet been reported in Thailand. Species, which did not correspond to any described taxa in scientific literature (new species or unknown modifications) are designated by "cf." or "sp.". © Czech Phycological Society (2011).